Study of Brewing Temperature and Time on Antioxidant Activity in Kratom Leaf Powder (Mitragyna speciosa Korth.) - Martha Christina; Purwayantie Sulvi; Suko Priyono (Universitas Tanjungpura, 2022)
Kratom (Mitragyna speciosa Korth.) is a plant commonly found in Kapuas Hulu that contains bioactive antioxidant compounds, such as alkaloids, flavonoids, phenols, terpenes, and saponins. The brewing process is one method that can be used to extract antioxidant compounds. The problem is that there is no research on the best temperature and time for brewing antioxidant compounds in kratom leaf powder. Therefore, this study aimed to determine the best time and temperature for the antioxidant activity of brewing kratom leaf powder. This study used a two-factor factorial Completely Randomized Block Design (RCBD) method consisting of 3 treatments of brewing temperature (70, 85, 95 Â°C) and brewing time (5, 10, 15 minutes) with 3 replications. The data obtained were analyzed using the ANOVA test (a=5%) followed by BNJ (a=5%). The best treatment was determined using the effectiveness index test. The parameters tested in this study consisted of total alkaloids, total flavonoids, total phenols, and antioxidant activity. The test results show that the best time and temperature treatment that produced the highest antioxidant activity value was 95Â°C, 15 minutes, with the characteristics of total alkaloids (13,589%), total flavonoids (30,754 mg QE/g), total phenol (12,258 mg GAE/g), activity antioxidants (91.543%).